Patients Surviving Critical COVID-19 have Impairments in Dual-task Performance Related to Post-intensive Care Syndrome. (July 2022) - Morelli, Nathan; Parry, Selina M.; Steele, Angela; Lusby, Megan; Montgomery-Yates, Ashley A.; Morris, Peter E.; Mayer, Kirby P.
Objective: The purpose was to examine Dual Task (DT) performance in patients surviving severe and critical COVID-19 compared to patients with chronic lung disease (CLD). Secondarily, we aimed to determine the psychometric properties of the Timed Up and Go (TUG) test in patients surviving COVID-19. Design: Prospective, cross-sectional, observational study. Setting: Academic medical center within United States. Patients: Ninety-two patients including 36 survivors of critical COVID-19 that required mechanical ventilation (critical-COVID), 20 patients recovering from COVID-19 that required supplemental oxygen with hospitalization (severe-COVID), and 36 patients with CLD serving as a control group. Measurements and Main Results: Patients completed the TUG, DT-TUG, Short Physical Performance Battery (SPPB), and Six Minute Walk Test (6MWT) 1-month after hospital discharge. A subset of patients returned at 3-months and repeated testing to determine the minimal detectable change (MDC). Critical-COVID group (16.8 ± 7.3) performed the DT-TUG in significantly slower than CLD group (13.9 ± 4.8 s; P = .024) and Severe-COVID group (13.1 ± 5.1 s; P = .025). Within-subject difference between TUG and DT-TUG was also significantly worse in critical-COVID group (−21%) compared to CLD (−10%; P = .012), even despite CLD patients having a higher comorbid burden ( P < .003) and older age ( P < .001). TUG and DT-TUG demonstrated strong to excellent construct validity to the chair rise test, gait speed, and 6MWT for both COVID-19 groups (r = −0.84to 0.73, P < .05). One- and 3-months after hospital discharge there was a floor effect of 14% (n = 5/36) and 5.2% (n = 1/19), respectively for patients in the critical-COVID group. Ceiling effects were noted in four (11%) critical-COVID, six (30%) severe-COVID patients for the TUG and DT-TUG at 1-month. Conclusion: The ability to maintain mobility performance in the presence of a cognitive DT is grossly impaired in patients surviving critical COVID-19. DT performance may subserve the understanding of impairments related to Post-intensive care syndrome (PICS) for survivors of critical illness.